IMPLEMENTASI KEBIJAKAN JKN OLEH PEMBERI PELAYANAN KESEHATAN DI KABUPATEN KEPULAUAN ANAMBAS - Irawati Sagala; Laksono Trisnantoro; Retna Siwi Padmawati (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Anambas Islands Regency is a district that is categorized as a DTPK area. In the health context, rural and remote areas are often associated with limited public transportation, poor road infrastructure, long distances to health care facilities and difficulties in recruiting and retaining health workers. As a result there is a significant impact on the provision of adequate health services. The availability of insufficient resources at every health facility in Anambas Islands Regency is also an obstacle because in implementing JKN every health facility in Anambas Islands Regency must meet the credentialing requirements set by BPJS Kesehatan. Objective: Analyzing the implementation of JKN policies by health service providers in Anambas Islands Regency. Methods: Descriptive research with qualitative methods using a single case study design Results: Implementation of policy NHI by health care providers both in health centers and hospitals are still many have constraints such as limited power specialist, especially in hospitals, general practitioners definitive still lacking in some health facilities, the limited infrastructure in health centers and hospitals that cause will not want the patient should be referred. This adds to the burden of transportation costs to society as ocean freight rates are quite expensive though some things can be addressed as a problem of information and improvement of bureaucratic structures, but it can not prevent the public to be referred. Conclusions: The implementation of the JKN policy is not suitable for implementation in Anambas Islands Regency as a DTPK area because the benefits received by the community from JKN are limited due to the many obstacles faced by health service providers.